PROVIDING EMPLOYMENT BY IMPROVING THE EFFICIENCY OF FAMILY BUSINESSES - Shadieva G.M.; Khusinova Shoira Akbarovna (Journal of new century innovations, 2023)
Abstract: In the article, the opinions about the socio-economic side of the development of family entrepreneurship in the conditions of the digital economy, the role and importance of family entrepreneurship in the national economy, as well as the ways to develop and increase the efficiency of family entrepreneurship are expressed, and also the statistics are given.